Callisthenics: a review (Research, Society and Development, 2020)
The aim of this work was to carry out a bibliographic review on the effects of calisthenics on increasing lean mass, increasing strength and physical endurance. Enabling contributions in the sports area and aiming at the practice of physical exercises without the need for gym equipment, associated with a good and adequate diet. This is an integrative literature review study, of a qualitative and exploratory nature, with a theoretical approach. The search for the articles was carried out in five electronic databases accessed in the Virtual Health Library (VHL): Medical Literature Analysis and Retrieval System online (Medline), Latin American and Caribbean Literature in Health Sciences (Lilacs), Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Google Scholar. Descriptors used, registered in the health sciences descriptors (DeCs): "Calisthenics", "Physical Analysis" and "Physical Activity". The research took place in March 2020. Twenty references related to the theme were found, of which twelve were excluded from this total because they did not fit the inclusion criteria, leaving six references that fit the study. Among the six articles found, those published between 2017 and 2018 prevailed with a total of 3 articles (50%), followed by other articles for the year 2011 to 2013 (50%). Therefore, it is concluded that calisthenics can be used as a way to increase muscle mass, increase physical strength and improve physical endurance and having one of the great advantages to practice outdoors and without any financial cost.